(untitled) (Research, Society and Development, 2021)
The present study had as objective to evaluate the resistance to torsion fracture of two instrumentation systems based on different motion cinematics: alternating movement of the system TF Adaptive and the rotary movement of the system HYFLEX CM. For this 15 TF Adaptive instruments were used to 27 mm in length, with the following dimensions: 20/.04, 25/.06, 35/04 and 30 Hyflex CM instruments to 25 mm in length, with the following dimensions: 25/.08, 20/.04, 25/04, 20/.06 , 30/.04 and 40/.04. The instruments were evaluated prior to your use and after two, four, six and eight use in simulated acrylic resin canals. These canals were standardized and their curvature was 35 degrees and their final length 18 mm, being this point reached at the end of the instrumentation in both systems. The variable in question was measured in degrees until the time of instrument fracture, obtained through a modified Troptômetro. The values registered at the time of fracture, for each instrument, were submitted to statistical analysis using the Wilcoxon test, Mann-Whitney U Test for comparison between the two systems of instrumentation (p ≥ 0.05). The results showed that both instruments did not show differences when evaluated without any use, after two uses, four uses, six uses and finally eight uses (p ≥ 0.05). It was concluded that TF Adaptive systems and Hyflex CM showed similarity as resistance to torsion fracture.